An optimized intermolecular force field for hydrogen‐bonded organic molecular crystals using atomic multipole electrostatics. Issue 4 (16th July 2016) - Pyzer-Knapp, Edward O.; Thompson, Hugh P. G.; Day, Graeme M.
Abstract : An empirically parameterized intermolecular force field is developed for crystal structure modelling and prediction. The model is optimized for use with an atomic multipole description of electrostatic interactions. Abstract : We present a re‐parameterization of a popular intermolecular force field for describing intermolecular interactions in the organic solid state. Specifically we optimize the performance of the exp‐6 force field when used in conjunction with atomic multipole electrostatics. We also parameterize force fields that are optimized for use with multipoles derived from polarized molecular electron densities, to account for induction effects in molecular crystals. Parameterization is performed against a set of 186 experimentally determined, low‐temperature crystal structures and 53 measured sublimation enthalpies of hydrogen‐bonding organic molecules. The resulting force fields are tested on a validation set of 129 crystal structures and show improved reproduction of the structures and lattice energies of a range of organic molecular crystals compared with the original force field with atomic partial charge electrostatics. Unit‐cell dimensions of the validation set are typically reproduced to within 3% with the re‐parameterized force fields. Lattice energies, which were all included during parameterization, are systematically underestimated when compared with measured sublimation enthalpies, with mean absolute errors of between 7.4 and 9.0%.